Photogrammetric Survey for the Architectural Restoration of Ecclesiastical Cultural Heritage Monuments: The Case Study of the Church of the Holy Cross in Tochni - Georgiou, Zoe; Philokyprou, Maria; Themistocleous, Kyriacos (My University, 2021)
This paper investigates the methodology of the digital documentation of an ecclesiastical monument in Tochni, Cyprus. The study very briefly describes the architectural history of the monument, as well as the changes that resulted in its current ruined condition. A photogrammetric survey of the monument was conducted to obtain its architectural elements, and subsequently conduct a restoration proposal. The aim of the survey is to investigate the use of photogrammetry using UAVs to examine historical monuments, in order to have a better understanding of the structure and elements that are difficult to measure and study in detail through traditional documentation.
Keywords: Digital capture; Digital media; Ecclesiastical monument; Monuments; Photogrammetry; UAV